THREATS TO FOOD SECURITY AND COMMON AGRICULTURAL POLICY - Mariola Kwasek (Ekonomika Poljoprivrede (1979), 2012)
The aim of this article is presented threats to food security in the context of the CAP after 2013. The main threats to food security are (1) world population growth, (2) the increase demand for food, (3) food price, (4) the disappearance of the variety of agricultural plant species (4) the increase in the area of scarcity water and the limitation of the availability of land and (5) the food losses and food waste. In the face of numerous threats to food security, the European Union needs a strong Common Agricultural Policy, which could succeed in feeding the constantly-growing population of a world. The reformed Common Agricultural Policy should provide food security, not only for the European Union, but on a global scale.